1999
DOI: 10.1074/jbc.274.11.7545
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid in Platelet Microparticles Up-regulates Cyclooxygenase-2-dependent Prostaglandin Formation via a Protein Kinase C/Mitogen-activated Protein Kinase-dependent Pathway

Abstract: Activation of platelets by agonists, such as collagen and thrombin, results in shedding of membrane microparticles (MP) 1 from their surface (1). Formation of MP results from an exocytotic budding process (2, 3) and may include both procoagulant (4, 5) and anticoagulant (6, 7) proteins when shed from platelets. Increased circulating concentrations of MP have been detected in vivo in syndromes of platelet activation (8, 9). It is likely that the shear forces in areas of disordered flow would favor MP formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
165
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(181 citation statements)
references
References 70 publications
(56 reference statements)
11
165
1
4
Order By: Relevance
“…Concordingly, it has been demonstrated that arachidonic acid of platelet microparticles induces COX-2 expression through a PI3-kinase-dependent pathway in a human monocytoid cell line (Barry et al, 1999). Our data are also in agreement with those obtained in di erent experimental systems showing that a PI3-kinase-dependent pathway mediates the proliferative e ects of IGF-I receptor (Dufourny et al, 1997;Rubin and Baserga, 1995).…”
Section: Discussionsupporting
confidence: 82%
“…Concordingly, it has been demonstrated that arachidonic acid of platelet microparticles induces COX-2 expression through a PI3-kinase-dependent pathway in a human monocytoid cell line (Barry et al, 1999). Our data are also in agreement with those obtained in di erent experimental systems showing that a PI3-kinase-dependent pathway mediates the proliferative e ects of IGF-I receptor (Dufourny et al, 1997;Rubin and Baserga, 1995).…”
Section: Discussionsupporting
confidence: 82%
“…Arachidonic acid is a major mediator of the cellular effects of microparticles (32,(37)(38)(39). We previously demonstrated that microparticles shuttle arachidonic acid from leukocytes to fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work 34 demonstrates that this is indeed the case, and future work will investigate the mechanism involved in this survivalpromoting response. The notion that AA causes translocation 35 and activation of protein kinase C, 36 as well as stimulation of extracellular signal-regulated kinases 1/2 phosphorylation, 37 is well established and these events were shown to prevent apoptosis. 38,39 Thus, the question to be answered is whether these pathways also mediate the protective effects of AA in the peroxynitrite-dependent necrotic response.…”
Section: Discussionmentioning
confidence: 99%